2003
DOI: 10.1046/j.1365-2265.2003.01820.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and β‐cell dysfunction in normoglycaemic European women with a history of gestational diabetes

Abstract: European normoglycaemic women with previous GDM display both glucoregulatory and antilipolytic insulin resistance, reduced beta-cell function and dyslipidaemia. These metabolic abnormalities are likely to contribute to their increased risk of future type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 57 publications
2
50
0
1
Order By: Relevance
“…Abnormalities in beta cell function as well as in insulin action have been described in other cohorts of women with a history of gestational diabetes [15,[37][38][39][40][41][42]. The heterogeneity between these studies is probably a result of the different ethnic and geographic origins of the populations studied.…”
Section: Discussionmentioning
confidence: 98%
“…Abnormalities in beta cell function as well as in insulin action have been described in other cohorts of women with a history of gestational diabetes [15,[37][38][39][40][41][42]. The heterogeneity between these studies is probably a result of the different ethnic and geographic origins of the populations studied.…”
Section: Discussionmentioning
confidence: 98%
“…The notion that some metabolic memory persists in women with prior GDM even when they present NGT has emerged from a number of previous studies [12][13][14][15][16][17][18][19]. The majority of these studies have clearly indicated that previous GDM is associated with a significant reduction in insulin sensitivity, insulin secretion or both in women who maintain NGT at follow-up [12][13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these studies have clearly indicated that previous GDM is associated with a significant reduction in insulin sensitivity, insulin secretion or both in women who maintain NGT at follow-up [12][13][14][15][16][17][18][19]. However, uncertainty remains as a result of some bias in the design of most of these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical assays were performed as described previously [5]. Of the women with pGDM, 227 out of 368 (62%) underwent a 75-g OGTT and the remainder (including 37 with known type 2 diabetes) had measurement of fasting glucose and HbA 1 c. The pGDM group was subdivided into two: pGDM with normal glucose regulation post-partum (NG) and pGDM with abnormal glucose regulation post-partum (AG) [4].…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%